Perception of the periphery by its residents of different cultural backgrounds in Israel. (13th November 2020) - Shamai, Shmuel; Gorbatkin, Denis; Arnon, Sara; Vitman, Adi
We studied perception of place in the northeastern Israeli periphery among residents from five culturally and economically distinguished locations. The attitudes towards place are structured and measured in categories of place dependence and place attachment, and as comparisons of the respondents' region of residence with the centre of Israel. The results show that 'personal factor' as a factor of place attachment has more impact on those who were born in or relocated to their settlements in childhood, while 'social factor' is more important for adult resettlers. The inter-settlement comparison demonstrates resemblance in attitudes towards place in the relatively prosperous settlements along with comparatively distinctive perception profiles in the least developed locations. The factors of economics, administration and infrastructure are less significant distinctive components of place dependence and centre-region comparison, whereas environmental and emotional factors are more significant distinguishers among residents from different locations.